Algorithm for Line Follower Robots to Follow Critical Paths with Minimum Number of Sensors - Chowdhury, Nakib Hayat; Khushi, Deloara; Rashid, Md. Mamunur (International Journal of Computer (IJC), 2017)
This paper introduces an approach which help a line follower robot to achieve the ability to autonomously follow a path that has straight lines, curve, 90 degree bends, T-junctions and + junctions using minimum sensors. Generally a line follower robot uses matrix of sensors to achieve this ability. This paper discuss about the algorithm through which a line follower can do the same thing using an array of sensor with minimum number of sensors. Because, if we able to decrease sensor number, we can decrease the complexity of the robot. Additionally, it also reduce the cost. But, here main challenge is ensuring efficiency. As we know, for a line follower robot, it is difficult to detect and follow T-junctions, 90 degree bends and grid junctions. To overcome this challenge, people add extra sensors to detect 90 degree bends, T-junctions and + junctions and design algorithm to follow them. If we reduce sensor, those robots will not able to detect these critical junctions and so, lose its efficiency. This paper discusses about line sensors configuration, their positions and also develop an algorithm so that a robot can follow a path with curve, 90 degree bends, T-junctions and + junctions using only four sensors.